(untitled) (Pedagogy of Higher and Secondary Education, 2009)
The Chinese music drama Kuncyuy in her parallel to liturgical drama - of Europe. The Article illuminates the questions history metaphysicians on example of the parallelismartistic event 15-16 ages upon their urgency for modem listeners.